The Ward Lock Encyclopedia of Practical Gardening - Pereire, Anita (London Ward Lock, 1999)
Features alphabetically-arranged entries that provide descriptions of over 4,000 flowers, trees, shrubs, climbing plants, and fruit, and includes information about gardening techniques, a quick-reference guide for planting, and more than 2,000 color photographs.
Include Index, Table, Graph and Illustration
Keywords: Gardening -- Plants, Ornamental -- Gardens